Fungal endophytes boost salt tolerance and seed quality in quinoa ecotypes along a latitudinal gradient - Miño, Roberto; Ballesteros, Gabriel I.; Ruiz, Karina B.; Acuña-Rodríguez, Ian S.; Molina-Montenegro, Marco A. (Frontiers in Plant Science, 2025)
Soil salinity threatens global food security, making salt tolerance a key agronomic trait. Quinoa (Chenopodium quinoa Willd.), a halophytic pseudo-cereal known for its high nutritional value, emerges as a promising candidate due to its inherent resilience to saline conditions. Although quinoa's physiological and morphological adaptations to salinity are documented, the role of native fungal endophytes in enhancing salinity tolerance remains largely unexplored, particularly across diverse genotypes. This study investigates the contributions of quinoa-associated endophytes to salinity tolerance and seed quality in different genotypes, thus contributing to understand ecological interactions bolstering crop resilience. To achieve this objective, five quinoa genotypes were selected based on their distribution along a 2,200 km latitudinal gradient (19°–39° S), representing a range of ecological niches. Plants with (E+) and without (E−) fungal endophytes were subjected to salinity treatments of 0, 200, and 400 mM NaCl. Salinity tolerance was assessed through photochemical efficiency, gene expression analysis of CqNHX1, and plant survival rates. Seed quality was evaluated by measuring seed weight and protein content, providing a comprehensive assessment of the endophytes' impact on quinoa under stress conditions. Our results reveal that native microbiomes significantly enhanced salinity tolerance and seed quality in a genotype-dependent manner. Notably, E+ plants demonstrated improved photochemical efficiency and higher expression levels of CqNHX1 under high salinity conditions, with survival rates increasing by up to 30% compared to E− plants. Seed weight and protein content were also positively affected, with E+ plants showing up to a 25% increase in protein content under 400 mM NaCl stress. Remarkably, E+ plants exhibited no negative effects under non-saline conditions. These findings suggest that fungal endophytes interactions shift from neutral to beneficial under salinity, with no trade-offs under normal conditions. This highlights the potential role of endophytes in enhancing quinoa resilience and nutritional value, reinforcing their importance for crop adaptation in the face of climate change. Future research should explore the molecular mechanisms underlying these beneficial interactions and assess their applicability to other crops, paving the way for innovative strategies in plant breeding and conservation.